2019
DOI: 10.31795/baunsobed.659297
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Local People’s Perceptions of Tourism Impact, Community Participation and Support for Tourism Development in the Development of Sustainable Tourism: Case of Beypazarı

Abstract: Balıkesir Üniversitesi Sosyal Bilimler Enstitüsü Dergisi Furthermore, despite community participation level is low, local people perceive the impact of tourism positively and support tourism development. Ensuring the participation of the local people is very important for the sustainable development of tourism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
0
4
0
4
Order By: Relevance
“…Accordingly, the support of residents to tourism will increase when residents have better perceptions of the positive economic outputs of tourism development. This argument is supported by much research in the literature (Jurowski et al, 1997;Stylidis and Terzidou, 2014;Rasoolimanesh et al, 2017;Segota et al, 2017;Sert, 2019). On the other hand, when the economic effects of tourism are perceived as negative by residents, their support for tourism decreases (Gursoy et al, 2002).…”
Section: Research Model and Hypothesesmentioning
confidence: 93%
See 3 more Smart Citations
“…Accordingly, the support of residents to tourism will increase when residents have better perceptions of the positive economic outputs of tourism development. This argument is supported by much research in the literature (Jurowski et al, 1997;Stylidis and Terzidou, 2014;Rasoolimanesh et al, 2017;Segota et al, 2017;Sert, 2019). On the other hand, when the economic effects of tourism are perceived as negative by residents, their support for tourism decreases (Gursoy et al, 2002).…”
Section: Research Model and Hypothesesmentioning
confidence: 93%
“…Having seen the relationship between the support of residents towards tourism development and the positive economic effects of tourism development, it is essential to draw attention to the relationship between the socio-cultural perceptions of tourism development and support for tourism. Some research in the literature showed that when the socio-cultural effects of tourism development perceived by residents are positive, residents supported tourism development (Cengiz and Kirkbir, 2007;Ertuna et al, 2012;Ozaltin Turker and Turker, 2014;Stylidis and Terzidou, 2014;Rasoolimanesh et al, 2017;Segota et al, 2017;Sert, 2019). On the other hand, some research in the literature showed that the support of residents towards tourism decreased when the negative effects of tourism development on the socio-cultural environment are perceived (Nunkoo and Ramkissoon 2011;Sert, 2019).…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Bir destinasyonda turizmin gelişmesi ile yerleşik halk kısa vadede, pek çok toplulukta olduğu gibi, istihdam oluşturma, gelir yaratma ve bölge alt yapısının gelişmesi gibi olumlu etkilerinden dolayı turizme olumlu yaklaşım sergilerken, sosyokültürel ve çevresel boyutundaki muhtemel olumsuz etkileri nedeniyle turizmi endişe verici bir olgu olarak algılayabilmektedir. Literatürde yer alan pek çok çalışmada yerel halkın (Meriç ve Erten, 2020;Ercan, 2019;Sert, 2019;Hançer ve Mancı, 2017;Mansuroğlu, 2006) ve yerel yöneticilerin (Akyol, Zengin, Akkaşoğlu ve Ulema, 2020), turizmin etkileri hakkındaki algılarına odaklanılmıştır. Bu çalışmalar, yerel paydaşların turizm gelişimine ilişkin algılarının anlaşılmasını sağlayarak, uygulayıcılara ve politika geliştiricilere daha iyi stratejiler geliştirilmesi için yol gösterici olmuştur (Chen, 2001:235).…”
Section: Introductionunclassified